Music Interventions in Hyperacute and Acute Stroke Patients: A Randomized Controlled Pilot Feasibility Study - Jeffrey J. Fletcher; Allison Edberg; Ronald Grifka; Joan Westendorp; Augusto Elias; Jacquie Knott; Elizabeth Martin; Fazeel Siddiqui (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Music interventions have been shown to have beneficial effects on hemodynamic parameters, pain, and anxiety in various medical settings. However, music interventions in the setting of acute stroke have not been studied. The objective of this trial was to perform a pilot feasibility study of music interventions in the setting of acute stroke to inform a larger efficacy trial. Methods Open label parallel group, randomized controlled trial with objective endpoints. Results The percentage of eligible patients approached for consent who were recruited into the trial was 85.7% (95% CI 75.9%–98%; 30/35) and the percentage of eligible patients recruited into the trial was 66.7% (95% CI 52.9%–80.4%; 30/45). Twenty‐nine participants completed the first 6 h of the trial 96.7% (95% CI 82.8%–99.9%, 29/30). Participants were highly supportive of music interventions in the target setting (mean value of 8 (SD ± 1.6) on a scale of 1–10). 95% Confidence Intervals for efficacy included clinically important differences. Specifically, the SBPV was non‐significantly lower in the intervention arm (mean difference − 1.31 mmHg, [95% CI −4.8 to 2.2 mmHg]). Similarly, the adjusted β was non‐significantly lower in the intervention arm for change in pain burden (−3.9 [95% CI −11.4 to 3.7]) and change in anxiety burden (−9.9 [−98.2 to 78.5]). Interpretation Our findings support a larger trial of music or sound interventions in hyperacute and acute stroke patients as alternatives to or synergists with pharmacologic management.